WhatsApp Use in Weight Intervention for Adults with Obesity - venti agustina; Syamsul Anwar; Ninik Yunitri (Indonesian Journal of Human Nutrition, 2024)
Unhealthy lifestyles are thought to contribute to the growing burden of obesity among adults, despite a preventable condition. Changing these behaviors requires appropriate and modern educational interventions. Social media platforms are increasingly used to contribute positively to supporting health behavior change. This study aimed to investigate the effect of using a social media module, specifically WhatsApp, on behavioral changes among adults with obesity. By using G-Power 3.1 software with an alpha level of 0.05, a power (1 - ß) of 0.95, an effect size of 0.64, and adding up to 10% buffer, the final sample consisted of 40 participants recruited using purposive random sampling based on inclusion and exclusion criteria. A pre-experimental one-group pre-test post-test design was conducted in this study. Data were collected using a questionnaire, biochemical markers, and anthropometry measurements, before and after intervention. Jamovi 2.3.28 software was used to test statistical analyses with a p-value < 0.05. Forty adult females (38.92 ± 3.79) participated in the six-week intervention. Significant relationships were found in knowledge (Z = -3.36, p = 0.003), attitudes (Z = -3.78, p = 0.001), and practices (Z = -8.90, p < 0.00) related to obesity. A significant shift in participants’ stages of behavioral change was also found (χ² = 17.8, p < 0.001), and waist circumference significantly decreased post-intervention (p < 0.001). No significant changes were observed in body weight (p = 0.323), BMI (p = 0.314), random blood glucose (p = 0.116), total cholesterol (p = 0.105), and uric acid (p = 0.058) after the intervention. Although the intervention did not significantly affect body weight, BMI, or biochemical profiles, the use of WhatsApp is an effective tool in improving knowledge, attitude, and practice related to obesity, shifting the stages of behavioral changes, and reducing waist circumference.